Microbiological Quality of Raw Donkey Milk from Serbia and Its Antibacterial Properties at Pre-Cooling Temperature - Ljubiša Šarić; Tamara Premović; Bojana Šarić; Ivana Čabarkapa; Olja Todorić; Jelena Miljanić; Jasmina Lazarević; Nedjeljko Karabasil (Animals, 2023)
The aim of this study was to examine the microbiological quality of raw donkey milk of an indigenous Serbian breed as well as the changes in the microbial populations during storage at 4 °C. In addition, antibacterial activity of donkey milk against E. coli, L. monocytogenes and S. aureus at 15 °C as well as the content of the two main antibacterial proteins lysozyme and lactoferrin were investigated. Microbiological examination of 137 individual milk samples collected over a period of 21 months showed good microbiological quality since foodborne pathogens such as Salmonella spp. and L. monocytogenes were not detected in any of the analyzed samples, while the number of E. coli, Enterobacteriaceae, total coliform bacteria, sulfite-reducing Clostridia and aerobic sporogenic bacteria was below the limit of quantification (<1 cfu mL−1). During the six-days storage at 4 °C, total bacterial counts and the counts of lactic acid bacteria remained at the initial level while pathogenic bacteria were not detected. The strongest antibacterial activity of the tested milk was observed against E. coli, while S. aureus was the least sensitive to milk antibacterial compounds. Although further research is needed to fully elucidate the antibacterial mechanism and synergistic activity of different compounds in donkey milk, the high content lysozyme (2.63 ± 0.03 g L−1) and lactoferrin (15.48 mg L−1) observed in tested milk could contribute to its strong antibacterial activity and extension of the storage period during which it can be safely consumed.